Rapid taurine and lactate biomarkers determination with disposable electrochemical detectors. (20th June 2017) - Revenga-Parra, M.; Martínez-Periñán, E.; Moreno, B.; Pariente, F.; Lorenzo, E.
Abstract: Taurine and lactate are biomarkers used for the diagnosis of different pathologies. In this study, a simple analytical approach for the direct determination of taurine and lactate in tears and saliva is described. The method is based on the use of single wall carbon nanotubes screen printed electrodes modified with films derived from the electropolymerization of a new Schiff base metallate, as liquid chromatography electrochemical detector. The new Schiff base metallate is the complex of nickel(II) with the ligand N, N′-bis(2, 4-dihydroxybenzylidene)-1, 2-diaminobenzene ([Ni II (2, 4DHS)]), which is electropolymerized in alkaline solution to give electroactive films strongly adhered on the electrode surface. These films present a potent and stable electrocatalytic activity toward the oxidation of taurine and lactate. Hence, the resulting modified electrodes, coupled to a chromatographic system, allow the quantification of these biomarkers directly in biological samples without need of derivatization schemes or sample pre-treatment.